The Relation Between Price, Product Quality, and Image of A Batik Brand Toward Customer Satisfaction - Tamamudin, Tamamudin (International Journal of Islamic Business and Economics (IJIBEC), 2017)
This study reviews whether there is a relation between price, product quality, and image of a batik brand toward customer satisfaction. This study uses quantitative research. The method that is used in collecting primary data is random sampling method. There are a hundred (100) responders as the sample of this study. The data in this study is obtained from questionnaire (primary), several observations, and direct interview with the party who is related to customer criteria that comes to buy Batik Tamina between July and September 2016. The analysis technique of this study is multiple regression analysis and the hypothesis test of this study is partial T-test and simultaneous F-test with less than 5% (0.05) of significance level, and Coefficient Determination Test (R2). The result of this study shows that price (X1) has a relation to customer satisfaction (Y) with 0.046<0.05 of significance level. Product quality (X2) has no significant relation to customer satisfaction (Y) with 0.138>0.05 of significance level. Partially, a brand’s image (X3) has a significant relation to customer satisfaction (Y) with 0.00>0.05 of significance level. The amount of the relation between price (X1), product quality variables (X2), and brand’s image variables (X3) toward the customer satisfaction variables (Y) is 40.5% while the rest (59.5) are explained by other factors that are not mentioned in this study.